Análisis técnico financiero de las alternativas de transporte para el proyecto refiBoyacá en el municipio de Duitama (2018)
The present degree work was carried out in order to evaluate the most efficient transport alternative for the REFIBOYACÁ project in the Municipality of Duitama for the company E.S.P. Energy Group SAS, based on the selection of one or more wells that meet the production characteristics and sales parameters for a modular refinery and, in turn, the most efficient transportation system to be able to evaluate what will be the corresponding design a port of discharge or the design of an oil pipeline, to finally determine the economic viability of it.